Pembentukan Karakter Religius Untuk Mereduksi Problem Remaja Putri Melalui Kajian An-Nisa - aas khasanah2323; Kartika Wulandari; Alief Budiyono (CV. ITTC INDONESIA, 2025)
Teenage girls' problems are the main problems that can hinder the development of young people's qualities. Therefore, there is a need for religious character formation to describe the formation of female students' religious character and the an-nisa study activities at MAN 2 Cilacap. This research uses a qualitative approach. Data sources consist of primary data sources and secondary data sources. The subjects in this research were class X students at MAN 2 Cilacap. Data collection techniques were carried out by means of interviews, observation and documentation. The results of this research show that the formation of religious character through the An-Nisa study at MAN 2 Cilacap which is attended by young women in class X every Friday coincides with young men carrying out Friday prayers. This An-Nisa study is one of the most effective solutions for building religious character in class women who are not studied in detail in class, for example menstruation, istihadloh, the morals of Muslim women, and the obligation to cover their private parts for Muslim women.